Delivery of isoniazid preventive therapy to reduce occupational TB among healthcare workers in Swaziland. Issue 1 (23rd March 2017) - Calnan, Marianne; Haumba, Samson; Matsebula, Makhosazana; Shongwe, Ntombifuthi; Pasipamire, Munyaradzi; Kruse Levy, Natalie; Mirira, Munamato; Preko, Peter; Smith-Arthur, Alisha; Ghazaryan, Varduhi
Abstract : Healthcare workers (HCWs) in Swaziland are at increased risk of acquiring tuberculosis (TB), but existing infection control and occupational health policies often fall short of mitigating the risk of acquiring TB in the workplace. Health service failure to systematically offer isoniazid preventive therapy (IPT) to HCWs, which is endorsed by the World Health Organisation (WHO), contributes significantly to the TB incidence among HCWs in high HIV prevalence settings. This paper describes a pilot introduction of IPT to HCWs, and expounds possible determinants for adherence and non-acceptance to IPT. Acceptance to the widespread use of IPT among HCWs can be improved through education on risk and counselling.